OPTIMALISASI PEMBANGUNAN DESA MELALUI PELATIHAN PERENCANAAN PEMBANGUNAN DESA BAGI SEKRETARIS DESA - Hutagalung, Simon Sumanjoyo; Utoyo, Bambang; Sulistio, Eko Budi; Puspawati, Ani Agus (Prosiding Pengabdian FISIP Unila, 2012)
This Community Services Activity is being carried out in South Lampung District Jatiagung with a lecture and discussion / FAQ. Meanwhile evaluation design used was a quantitative evaluation through pre test and post test. Also evaluated qualitatively through discussion / question and answer with monitoring during the extension / dissemination of the material presented during the process of counseling / socialization takes place between the presenters material with participants socialization, particularly with regard to the aspects related to Rural Development Planning. It can be concluded already understand the concept of Regional Planning and outline the content of their policies in the Indonesian Government regulations by members of the village in the district secretaries forum Jatiagung South Lampung regency. It has also been understood mechanisms and normative regulations in Rural Development Planning and the position of rural community participation in the activities of the Rural Development Plan by the members of the village in the district secretaries forum Jatiagung South Lampung regency. Keywords: Development Planning, Rural Assembly